2015
DOI: 10.4314/sajg.v4i4.8
|View full text |Cite
|
Sign up to set email alerts
|

Remote sensing bio-control damage on aquatic invasive alien plant species

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Further, Williams and Hunt [14] reported a 95% overall accuracy for mapping leafy spurge (Euphorbia esula L.) using the Airborne Visible/Infrared Spectrometer (AVIRIS) hyperspectral data. Notwithstanding these successful attempts, currently, using hyperspectral data in mapping IAPs has several limitations such as the high cost of satellite hyperspectral data, airborne and handheld sensors as well as the resultant large volumes of data that require high computing power for processing [15].…”
Section: Introductionmentioning
confidence: 99%
“…Further, Williams and Hunt [14] reported a 95% overall accuracy for mapping leafy spurge (Euphorbia esula L.) using the Airborne Visible/Infrared Spectrometer (AVIRIS) hyperspectral data. Notwithstanding these successful attempts, currently, using hyperspectral data in mapping IAPs has several limitations such as the high cost of satellite hyperspectral data, airborne and handheld sensors as well as the resultant large volumes of data that require high computing power for processing [15].…”
Section: Introductionmentioning
confidence: 99%
“…The normalized mean absolute error (NMEA) [28], root mean square error (RMSE), reliability index (RI) [21] and correlation coefficient (r) are given in Eqs. (3)-(6) [17].…”
Section: Test Statistics For Validating Transformation Parametersmentioning
confidence: 99%
“…The performance of both models in estimating T m remains widely unknown on the African continent. Nevertheless, a study by Isioye et al (2015b) on the performance of the UNB3m and GPT2w models revealed the performances of the duo models in estimating ZTD on the African continent.…”
Section: Introductionmentioning
confidence: 99%
“…Isioye et al (2015b) have demonstrated the efficacy of these model performance indicators and their mathematical formulations are contained therein.The NMAE measures the absolute difference between the forecasted values (from NWMTE-I, NWMTE-II, NWMTE-III, Bevis, UNB3m, GPT2w and GWMT-IV models) and the reference (integral method), normalized to the mean. AnNMAE value of zero indicates a perfect agreement.…”
mentioning
confidence: 99%